2019
DOI: 10.3386/w25965
|View full text |Cite
|
Sign up to set email alerts
|

Taking Stock of Trade Policy Uncertainty: Evidence from China’s Pre-WTO Accession

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
(36 reference statements)
0
17
1
Order By: Relevance
“…Approvals usually occurred in July-September of each year, and several studies noted a relationship between approval timing and trade flows. For instance, Alessandria, Khan, and Khederlarian (2019) found that trade flows increased especially in the months preceding the annual renewal of NTR by the U.S. Congress, that is TPU increased trade. Their empirical model with intrayear variation employed the gap between NTR and non-NTR tariffs, which were as high as 30% for several industries, as the measure of uncertainty.…”
Section: Uncertainty From Binding Overhangmentioning
confidence: 99%
See 1 more Smart Citation
“…Approvals usually occurred in July-September of each year, and several studies noted a relationship between approval timing and trade flows. For instance, Alessandria, Khan, and Khederlarian (2019) found that trade flows increased especially in the months preceding the annual renewal of NTR by the U.S. Congress, that is TPU increased trade. Their empirical model with intrayear variation employed the gap between NTR and non-NTR tariffs, which were as high as 30% for several industries, as the measure of uncertainty.…”
Section: Uncertainty From Binding Overhangmentioning
confidence: 99%
“…The issue of trade policy uncertainty is not new: Episodes of trade disputes among major economies have been well documented, for example Urata (2019) on the US-Japan dispute during the 1980s leading to voluntary export restraints (VER) and import expansion by Japan; Ling, Li, and Swenson (2017) on China's pre-WTO accession and others. Nonetheless, the recent episode takes on significance given the depth of global integration and the uncertainty surrounding these trade restrictions (Handley and Limao 2017;Crowley, Meng, and Song 2018;Alessandria, Khan, and Khederlarian 2019;Steinberg 2019;Amiti, Kong, and Weinstein 2019b;Caldara et al 2020). For instance, figure 1 from the World Trade Organization (WTO) shows the extent of uncertainty in trade policy in the last two years, i.e., a spike in trade restrictive measures imposed by countries and their trade coverage in 2018 and 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Handley and Limão (2017) show this has important price and welfare e¤ects and extend this logic to entry and technology-upgrading decisions but not to global sourcing decisions. Uncertainty can also a¤ect exports via inventory e¤ects(Alessandria et al, 2019).…”
mentioning
confidence: 99%
“…An alternative ap-proach for capturing the consequences of trade policy uncertainty turns instead to the estimation of structural models (Steinberg, 2019). 6 Alessandria et al (2019) use within year timing of TPU prior to China's WTO accession to quantify TPU, and our work allows us to identify the timing of TPU effects, including the short-to medium-run changes. 7 This paper also contributes to a literature that has studied the impact of trade policies or trade shocks on Chinese firms.…”
Section: Contribution To the Literaturementioning
confidence: 99%